2010
DOI: 10.1017/s1460396910000087
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as prevention of radiation-induced diarrhoea

Abstract: Aim: To assess the efficacy of a probiotic preparation on the prevention of radiation-induced diarrhoea in cancer patients.Methods: Group of 42 radio-oncology patients who had undergone adjuvant post-operative radiation therapy (RT) after abdominal and pelvic cancer were randomised to receive either the probiotic preparation "5'' Strain Dophilus (twice per day; L-Group), or the preparation Hylak Tropfen Forte (40 drops, three times per day; H-Group). Supplementation started on the first day and lasted until th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
1
27
1
1
Order By: Relevance
“…30 One ineligible study did not provide the number of people suffering from diarrhea. 16 The third study was excluded because of its follow-up study in Delia et al 20,33 Quality assessment The risk of bias for each RCT is displayed in Figure 2, and the risk of bias across all RCTs is displayed in Figure 3. These indicated generally good methodological quality.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…30 One ineligible study did not provide the number of people suffering from diarrhea. 16 The third study was excluded because of its follow-up study in Delia et al 20,33 Quality assessment The risk of bias for each RCT is displayed in Figure 2, and the risk of bias across all RCTs is displayed in Figure 3. These indicated generally good methodological quality.…”
Section: Included Studiesmentioning
confidence: 99%
“…As displayed in Supplementary Table S1, of the 11 studies, seven studies had no AEs caused by probiotics in prevention of chemoradiotherapy-induced diarrhea, [14][15][16][17]19,20,29 whereas four studies reported AEs with varying degrees in their treatment. 5,21,30,31 The 11 studies included 1612 people (873 consuming probiotics and 739 not consuming probiotics).…”
Section: Safety Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a smaller-scale randomized trial of 42 radio-oncology patients who had undergone adjuvant postoperative radiation therapy after abdominal and pelvic cancer, of which only 10 had been treated for CRC, either the probiotic preparation '5' Strain Dophilus (twice per day; L-group) or the preparation Hylak Tropfen Forte (40 drops, three times per day; H-group) were supplemented, starting on the first day and lasting until the end of radiotherapy [75]. The mean daily number of bowel movements was 4.16 in the L-group and 2.52 in the H-group.…”
Section: Adjuvant Treatment-related Toxicitymentioning
confidence: 99%
“…Of the patients in the L-group, 9% required antibiotics administration, compared with 25% in the H-group. The authors concluded that the prophylactic probiotic therapy produced a highly favorable benefit/risk ratio [75]. The few available trials and the presence of significant clinical and statistical heterogeneity limit the potential for robust evidence, but the results are pretty encouraging.…”
Section: Adjuvant Treatment-related Toxicitymentioning
confidence: 99%